(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2013)
Certain Buddhist statues discovered in Southeast Asia were sculpted after Sarnath-style sculptures. Thus, these statues were produced between the late fifth and early sixth centuries. Considering the sea route during that period, it was natural that Buddhist statues would be introduced from Sarnath to Funan in its prime via the Ganges and the Indian Ocean. Buddhist sculptures conveyed through that channel became the foundation for early Buddhist art in Southeast Asia. Based on the style created at Sarnath in India, this art is significant because it reveals the first stage of Buddhist art in Southeast Asia. These Buddhist sculptures reflect the Central and Southern Indian styles of the Gupta period. Hence, Buddhist art forms must have spread to Southeast Asia by different routes. Certain sculptures that were recently excavated in Shandong have no traces of drapery and have slender physical outlines. Such features were most likely influenced by styles employed in Sarnath Buddhist sculptures. These Shandong sculptures were most likely modelled after Buddhist statues discovered in Southeast Asian regions such as Thailand, Cambodia, and Vietnam, indicating that Central Indian Buddhist art was introduced earlier than Southern Indian art and conveyed from the Ganges to the South China Sea through the Gulf of Bengal via the sea routes. Thus, Southeast Asian Buddhist sculpture was the "missing link" that connected Central India to East China, and it was highly valuable as the first stage in the area.